The Site and the Familiar: A Collaborative Outpost on South Georgia Island - Hammer, Davis (My University, 2013)
This thesis proposes that the scientists, artists and climbers already drawn to South Georgia Island need a place to live and work that is more intimately connected to the natural and cultural phenomena of the site. It draws from these elements explicitly and implicitly, exploring the site intensely to create architecture that responds to the collected understanding. The island is remote, nearly a thousand miles from the closest inhabited land. It was once the center of the whaling industry in the South Atlantic but is now home only to a small research contingent and a whaling museum for tourists en route to Antarctica. The whaling station has fallen to ruin, slowly melding into the landscape, and time has wiped away the whale blood from its empty surfaces. The project took the form of a faceted wall nested in the hillside. Concrete walls mark the slope of the topography and a wooden frame rests lightly above, pushing out into the site to create relief from the narrow wall and allow spaces for the program and for informal interactions. The building acts as a datum, a measure against the ever-changing landscape that registers the winter snow drifts and the spring streams that carve into the hillside.
Thesis (Master's)--University of Washington, 2012
Keywords: Architecture; architecture